Analysis of Public Understanding of Online Loans in Banten Viewed from Financial Literacy and Consumptive Behavior with Financial Inclusion as an Intervening Variable - Adysta Carina Tawakal; Basrowi Basrowi; RR. Andriani Sariwardani (Jurnal Economic Resource, 2026)
This study analyzes the influence of financial literacy and consumptive behavior on understanding of online loans in Banten, with financial inclusion as an intervening variable. The rapid growth of fintech lending in Indonesia has facilitated access to financing but has also raised risks such as loan defaults, misuse of personal data, and the proliferation of illegal lending. A quantitative approach was employed using primary data collected through questionnaires. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with path analysis. Sampling using purposive sampling method and obtained samples of 398 respondents. The results indicate that financial literacy has a significant positive effect on understanding online loans and on financial inclusion. Consumptive behavior has a significant negative effect on understanding online loans but no significant effect on financial inclusion. Financial inclusion has a significant positive effect on understanding online loans and mediates the effect of financial literacy on understanding online loans. Conversely, consumptive behavior has no significant indirect effect through financial inclusion. These findings highlight the importance of improving financial literacy to enhance financial inclusion and strengthen public understanding of online lending services.